Analysis of Waveguides Containing EMCs (electromagnetic conductors) or PEMCs (perfect electromagnetic conductors) - Prudêncio, F. (2014)
The concept of a perfect electromagnetic conductor (PEMC) was introduced to generalize and unify two well-known and apparently disjoint concepts in electromagnetics: the perfect electric conductor (PEC) and the perfect magnetic conductor (PMC). Although the PEMC has proven a fertile tool in electromagnetic analyses dealing with new and complex boundaries, its corresponding definition as a medium has, nevertheless, raised several problems. In fact, according to its initial 3D definition, the PEMC cannot be considered a unique and well-defined medium: it leads to extraneous fields without physical meaning. By using a previously published generalization of a PEMC that regards this concept both as a boundary and as a medium - which was dubbed an MIM (Minkowskian isotropic medium) and acts, in practice, as an actual electromagnetic conductor (EMC) - it is herein presented a straightforward analysis of waveguides containing PEMCs that readily and systematically follows from the general framework of waveguides containing EMCs